Chemical caressess: geographical variation of male sexual signals in a Neotropical scorpion - Olivero, Paola Andrea (2015)
Differences in sexual signals among species are common, and may influence mate recognition and reproductive isolation. In scorpions, behavioural mechanisms and other sexual signals involved in mate selection and reproductive isolation have been scarcely studied. In this paper, we compare different male sexual signals between two distant populations of the scorpion Bothriurus bonariensis, one located in Uruguay and the other in Central Argentina. We compare sexual behaviours from intra-populations and inter-populations matings. In addition, we extent this comparison to the secreted compounds and morphology of the exocrine glands located on the dorsal side of telson in this species.  Males of B. bonariensis performed stimulatory behaviours to the female with different frequency of occurrence and duration in the two populations. Chemical analyses of the glandular extracts showed that Uruguayan males present compounds which are absent in males of Argentinian population. In addition, we observed that in inter-population matings, stimulatory behaviours had intermediate patterns to intra-population matings. However, males failed to achieve a successful sperm transfer with females of different population. Mechanisms of sexual isolation between these two distant populations of B. bonariensis apparently seem to have evolved due to divergence in allopatry. The differences in stimulatory levels during courtship between the two populations studied here give evidence for an early behavioural divergence promoted by sexual selection.